2015
DOI: 10.1111/joim.12390
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and cardiovascular diseases: where do we stand today?

Abstract: Abstract. Klatsky AL (Northern California Kaiser Permanente, Oakland, CA, USA). Alcohol and cardiovascular diseases: where do we stand today?. (Review). J Intern Med 2015;278: 238-250.For centuries, multiple medical risks of heavy alcohol drinking have been evident with simultaneous awareness of a less harmful or sensible drinking limit. The increased risks of heavy drinking, defined as three or more standard-sized drinks per day, are both cardiovascular (CV) and non-CV. The CV risks include the following: (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
109
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 96 publications
(152 reference statements)
0
109
1
5
Order By: Relevance
“…Acute alcohol consumption also decreases atrial current densities 41. Symptoms in patients with alcoholic cardiomyopathy include arrhythmias and heart failure, and are in accordance with reduced cardiac output 11. Even moderate alcohol consumption represents a risk factor for atrial fibrillation 43.…”
Section: Alcoholic Heart Disease and Alcoholic Liver Cirrhosismentioning
confidence: 90%
See 4 more Smart Citations
“…Acute alcohol consumption also decreases atrial current densities 41. Symptoms in patients with alcoholic cardiomyopathy include arrhythmias and heart failure, and are in accordance with reduced cardiac output 11. Even moderate alcohol consumption represents a risk factor for atrial fibrillation 43.…”
Section: Alcoholic Heart Disease and Alcoholic Liver Cirrhosismentioning
confidence: 90%
“…Between 23% and 40% of patients with cardiomyopathy develop the condition due to alcohol 39. It is estimated that significantly less chronic alcoholics develop alcoholic cardiomyopathy than the 15%–20% that develop liver cirrhosis 11. It has also been reported that alcoholic heart disease and alcoholic liver disease coexist in 10%–20% of patients with cirrhosis 4 5.…”
Section: Alcoholic Heart Disease and Alcoholic Liver Cirrhosismentioning
confidence: 99%
See 3 more Smart Citations